Platelets Play Differential Role During the Initiation and Progression of Autoimmune Neuroinflammation. Issue 9 (9th October 2015) - Starossom, Sarah C.; Veremeyko, Tatyana; Yung, Amanda W.Y.; Dukhinova, Marina; Au, Cheryl; Lau, Alexander Y.; Weiner, Howard L.; Ponomarev, Eugene D.
Abstract : Rationale : Platelets are known to participate in vascular pathologies; however, their role in neuroinflammatory diseases, such as multiple sclerosis (MS), is unknown. Autoimmune CD4 T cells have been the main focus of studies of MS, although the factors that regulate T-cell differentiation toward pathogenic T helper-1/T helper-17 phenotypes are not completely understood. Objective : We investigated the role of platelets in the modulation of CD4 T-cell functions in patients with MS and in mice with experimental autoimmune encephalitis, an animal model for MS. Methods and Results : We found that early in MS and experimental autoimmune encephalitis, platelets degranulated and produced soluble factors serotonin (5-hydroxytryptamine), platelet factor 4, and platelet-activating factor, which specifically stimulated differentiation of T cells toward pathogenic T helper-1, T helper-17, and interferon-γ/interleukin-17–producing CD4 T cells. At the later stages of MS and experimental autoimmune encephalitis, platelets became exhausted in their ability to produce proinflammatory factors and stimulate CD4 T cells but substantially increased their ability to form aggregates with CD4 T cells. Formation of platelet–CD4 T-cell aggregates involved the interaction of CD62P on activated platelets with adhesion molecule CD166 on activated CD4 T cells, contributing to downmodulation of CD4 T-cell activation, proliferation, and production of interferon-γ. Blocking of formation of platelet–CD4 T-cell aggregates during progression of experimental autoimmune encephalitis substantially enhanced proliferation of CD4 T cells in the central nervous system and the periphery leading to exacerbation of the disease. Conclusion : Our study indicates differential roles for platelets in the regulation of functions of pathogenic CD4 T cells during initiation and progression of central nervous system autoimmune inflammation. Abstract : Supplemental Digital Content is available in the text.